Pengaruh Kecemasan Ibu Hamil terhadap Peminatan Vaksinasi Covid-19 di Puskesmas Kunir - Andira, Juwita Ayu; Hamim, Nur; Ermawati, Iit (NHM PRESS, 2023)
An increase in the anxiety of pregnant women of the COVID-19 is due to the lack of knowledge of pregnant women about COVID-19 and how to prevent it. Anxiety experienced can reduce the immunity of pregnant women so that they can be more susceptible to infection. The purpose was to determine the effect of pregnant women's anxiety on the specialization of covid 19 vaccination at the Kunir Health Center. This research is quantitative research with cross sectional approach. The sample was pregnant women who had ANC visits and had not been vaccinated against COVID-19 at the Kunir Health Center as many as 45 respondents using the total sampling technique with the sperman rho test. The results showed that most of the respondents had a mild level of anxiety as many as 55.6% and an interest in the Covid 19 vaccine in the moderate interest category as many as 42.2%. From the Spearman's rho test was found that the p value <0.05( p = 0.000), which means that there is an influence of pregnant women's anxiety on the interest in Covid 19 vaccination at the Kunir Health Center. It is recommended that midwives always behave educatingly while in the community so that they can be used as role models in implementing health protocols and using vaccines.